2020
DOI: 10.1038/s41598-020-59497-z
|View full text |Cite
|
Sign up to set email alerts
|

Cats with thermal burn injuries from California wildfires show echocardiographic evidence of myocardial thickening and intracardiac thrombi

Abstract: Recent increases in the prevalence and severity of wildfires in some regions have resulted in an increased frequency of veterinary burn patients. few studies exist regarding diagnostics and management of burn wounds in veterinary patients and current knowledge is extrapolated from human literature and research models. Post-burn cardiac injury is a common finding and predictor of mortality in human patients and echocardiography is an important tool in monitoring response to therapy and predicting outcome. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 51 publications
0
28
0
1
Order By: Relevance
“…Antecedent events are common, with the most frequent being an anesthetic event or trauma, notably thermal burn injury. 62 Corticosteroid administration is a recognized antecedent event in cats being presented in heart failure, and this is true for both TMT and HCM (see Part 3). 6,61,64 LV wall thickness normalizes over 2-5 months.…”
Section: Jfms Clinical Practice 1031mentioning
confidence: 99%
See 1 more Smart Citation
“…Antecedent events are common, with the most frequent being an anesthetic event or trauma, notably thermal burn injury. 62 Corticosteroid administration is a recognized antecedent event in cats being presented in heart failure, and this is true for both TMT and HCM (see Part 3). 6,61,64 LV wall thickness normalizes over 2-5 months.…”
Section: Jfms Clinical Practice 1031mentioning
confidence: 99%
“…65 Chemotherapy can result in resolution of the thickening. [61][62][63] The principal case series describing this entity noted LA enlargement and left heart failure at presentation, but greater awareness may reveal milder cases in the future. 61 As with HCM, male domestic shorthairs are most commonly affected.…”
Section: Jfms Clinical Practice 1031mentioning
confidence: 99%
“…In einer Studie zu kardialen Veränderungen von Katzen mit Verbrennungen und Rauchvergiftungen im Zuge der vor kurzem aufgetretenen großen kalifornischen Waldbrände wurden echokardiografisch neben weiteren Veränderungen in 35 % der Fälle myokardiale Verdickungen nachgewiesen. Eine echokardiografische Kontrolle bei überlebenden Patienten erfolgte nicht [19].…”
Section: Diskussionunclassified
“…Few to no health impacts on cattle were reported in the review, however, there were no studies available directly evaluating the impacts of smoke exposure in these animals [ 52 ]. Researchers at the University of California, Davis, recently published a study on cats hospitalized with burns and smoke inhalation following the 2017–2018 California wildfires; the cats were shown to have significant cardiovascular changes based on serial echocardiograms [ 53 ]. Rhesus macaques housed at the California National Primate Research Center and naturally exposed to wildfire smoke were reported to have pregnancy losses following heavy smoke exposure [ 54 ].…”
Section: Introductionmentioning
confidence: 99%